LibNPDB: The First Freely Accessible Database of Libyan Natural Products - Abdelkarim Sasi; Ali Rafieda; Abrar Al-najjar; Arwa Jhan (AlQalam Journal of Medical and Applied Sciences, 2025)
Libya’s rich flora is a significant but untapped resource for natural products research. A lack of accessible digital information has limited progress in this area. To address this gap, we systematically collected data on bioactive compounds from Libyan plants, gathering information from various local records and existing online databases. This effort resulted in the Libyan Natural Products Database (LibNPDB), the first free, web-based repository for Libyan natural products. It currently holds 1,047 entries from scientific literature, covering 562 unique chemical compounds. As a powerful tool, LibNPDB allows users to search in multiple ways, such as by compound name, plant part, or plant source, and other parameters, providing researchers with a user-friendly interface to find data. Beyond being a comprehensive reference, the database aims to increase the global visibility of Libyan natural product research. Future developments include expanding the data on plant phytochemicals, adding more information on Libyan medicinal plants, improving the search filtrations and analysis tools, and enabling users to download data in bulk. These planned improvements will make the database more useful for advanced applications like virtual screening, molecular docking, and drug discovery. Ultimately, the LibNPDB (available at https://www.libnpdb.ly) is an essential resource for unlocking the scientific and economic potential of Libya’s natural resources while encouraging collaboration and innovation within the global research community.